Immobilized Organic Photosensitizers with Versatile Reactivity for Various Visible‐Light Applications1. (25th October 2013) - Ronzani, Filippo; Saint‐Cricq, Philippe; Arzoumanian, Emmanuel; Pigot, Thierry; Blanc, Sylvie; Oelgemöller, Michael; Oliveros, Esther; Richard, Claire; Lacombe, Sylvie
Abstract Various photosensitizers were grafted by conventional peptide coupling methods to functionalized silica with several macroscopic shapes (powders, films) or embedded in highly transparent and microporous silica xerogel monoliths. Owing to the transparency and free‐standing shape of the monoliths, the transient species arising from irradiation of the PSs could be analyzed and were not strikingly different from those observed in solutions. The observed reactivity for either liquid–solid (α‐terpinene oxygenation vs dehydrogenation) or gas–solid (dimethylsulfide, DMS, solvent‐free oxidation) reactions was consistent with the properties of the excited states of the PSs under consideration. Immobilized anthraquinone‐derived materials preferentially react in both cases by electron transfer from the substrate to the triplet state of the sensitizer, in spite of an efficient singlet oxygen production. The recently developed 9, 14‐dicyanobenzo[b]triphenylene‐3‐carboxylic acid, DBTP‐COOH, efficiently reacts via energy transfer to yield singlet oxygen from its triplet state. It was shown to perform better than 9, 10‐dicyanoanthracene and rose bengal for DMS oxidation and α‐terpinene photooxygenation to ascaridole, respectively. Thus, by a proper choice of the organic immobilized photocatalyst, it is possible to develop efficient and reusable materials, activated under visible light, for various applications and to tune the reaction pathway, opening the way to green oxidation processes.